Empowering Teachers and Parents in Integrative Holistic Early Childhood Education - Mulyanti Mulyanti (Universitas 'Aisyiyah Bandung, 2025)
Integrative Holistic Early Childhood Education is a comprehensive approach for children aged 0–6 years that integrates education, health, nutrition, and well-being; however, its implementation is often hindered by limited training and educational materials for early childhood education administrators on child nutrition and simple health assessments, as well as low parental awareness of healthy nutrition for young children. In Bandung Regency, the target proportion of undernourished toddlers is set below 15%, yet Community Health Centre data indicate that only 62.8% of toddlers experienced weight gain, which remains below the target of 90%. Early Childhood Education Patriot, located within the working area of the Bojongsoang Community Health Centre, Bandung Regency, was selected as the site for this community service programme, which aimed to improve parents’ knowledge and teachers’ skills related to early childhood growth and development screening. The programme consisted of structured seminars for parents and practical training sessions for teachers delivered by professional midwifery educators, involving six teachers, 20 parents, and 28 early childhood education students. Following the intervention, parents’ average knowledge scores increased from 67 to 82, while teachers’ knowledge scores improved by an average of 7.8 points and their practical skills by an average of 17.66 points. In conclusion, the seminars and training had a positive impact on parents’ knowledge of balanced nutrition and enhanced teachers’ knowledge and skills in conducting simple early childhood screening, supporting the need for sustained collaboration between educational institutions and local health centres